German public finances: Recent experiences and future challenges - Jürgen von Hagen; Rolf R. Strauch (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2001)
German public finances are currently subject to considerable changes in the macro-economic environment and this is probably only the beginning of more far-reaching developments in the future. Like many other European countries, Germany, on the one hand, faces the fiscal problems emerging from an ageing population, which will put upward pressure on social security expenditures. On the other hand, the public will reject an increase of the already high tax burden and an increasingly globalized economy and further European integration may put an additional limit on the government's capability to raise additional revenues. Finally, German governments will have to show whether they are able to meet these conflicting challenges in the future within the fiscal framework set by the Maastricht Treaty and the Stability and Growth Pact. Therefore, continued debt accumulation does not seem to be a viable option to circumvent the ageing problem and the limit on taxation. Thus we see three challenges for German public finances in the future. In this paper, we develop the recent history of German fiscal policy as a background to judging how fit Germany is to meet these challenges. Our main focus is on the government's fiscal strategies and the gradual erosion of the institutions that secured Germany's fiscal stability in the past.
Keywords: 330; Finanzpolitik; Standortwettbewerb; Sozialstaat; Konvergenzkriterien; Deutschland; Alternde Bevölkerung